Abolition of the obligation to cease an occupation for acknowledgment of an occupational skin disease: Backgrounds and perspectives. (25th March 2021) - Elsner, Peter
Summary: The occupational disease skin No. 5101 ("severe or recurrent skin diseases that have forced the patient to refrain from all activities that were or could be the cause of the development, aggravation or resurgence of the disease") is the most frequently notified occupational disease in Germany. Since 1936, the medical‐objective obligation to refrain from risky work activities, which has been necessary for the recognition of this occupational disease, was intended to delimit trivial diseases, facilitate the determination of occupational causality and promote prevention. The abolition of the legal obligation to refrain from risky work activities as a criterion for the recognition of the occupational disease 5101 as of 01.01.2021 has significant effects on the occupational dermatological care and expert assessment of this occupational disease. For less severe occupational skin diseases, however, the preventive dermatologist's procedure established since 1972 will continue to apply.